GIANT GASTRIC LIPOMA: A CASE REPORT AND LITERATURE REVIEW - Martins, Ruben (2024)
Introduction: Gastric lipomas are rare and defined as giant when they are greater than 4 cm, which is exceedingly rare. Most of them are asymptomatic; however, some symptoms may occur due to complications such as ulceration, digestive bleeding, or gastric obstruction. Case report: A 63-year-old male patient presented with early satiety, dyspepsia, and one episode of melena. Investigation revealed a ulcerated polypoid lesion, suggestive of a lipoma, in the antrum measuring approximately 7cm. The patient was discussed in a multidisciplinary meeting, and laparoscopic enucleation was proposed. The surgery and post-operative period were uneventful. Literature review: A total of 40 surgically treated cases of giant gastric lipomas are reported in the literature. The average age at presentation is 55, and the most common symptoms are melena (56%), hematemesis (29%), and epigastric pain (29%). In more than half of the cases, an ulcer is present. On computed tomography, most lesions are well-defined, homogeneous, submucosal, and composed of fat, which is practically pathognomonic. Discussion: This rare condition should be managed by a multidisciplinary team. We recommend endoscopic techniques for lesions up to 4cm and surgical management for larger lesions. Minimally invasive surgery should be preferred, and enucleation should be the standard procedure.